Comparative Analysis of Proteomic of Curcumin Reversing Multidrug Resistance in HCT-8/VCR Cells. (25th April 2022) - Li, Lei; Yu, Libo; Cao, Xiansheng; Zhang, Chao; Liu, Qi; Chen, Jun
Abstract : To further explore the mechanisms of curcumin reversing multidrug resistance (MDR) in HCT8/VCR cells. Here, we employed comparative analysis of proteomic of essential proteins of human colon carcinoma HCT8/VCR cells with or without treatment of curcumin by separating and quantifying the essential protein posttranslational modification through radical-free two-dimensional polyacrylamide gel electrophoresis with strong reductant. The reverse impact of curcumin on multidrug resistance of HCT8/VCR and HCT8/VCR cells was evaluated using MTT assay. After adding curcumin 25 μ M for 72 h, by 2-DE and mass spectrometry, twenty proteins were certified with changed expression levels. Three protein sites were upregulated and seventeen protein sites were downregulated in curcumin-treated HCT-8/VCR. Verification analyses were conducted using RT-PCR and Western blotting for downregulated proteins including GSTP1 and PRDX6. The proteins might have a direct or indirect contact with multidrug resistance. The finding of the research would provide novel sights for systematically comprehending the mechanisms of the reversal impacts of curcumin on MDR in HCT8/VCR cells and contribute to the recognition and application of new markers in clinical practice.